The relationship between level of diversifications and the performance of selected companies in Bursa Malaysia / Nurul Hazwani Mustafar - Mustafar, Nurul Hazwani (2017)
Diversification is a common strategic planning that most managers will do in order to expand their business and enhance their firms performance but how related it is to the firms' performance is still questionable to this day (T. Ravichandran, Yu Liu, Shu Han & Iftekhar Hasan (2009)). Studies done before stated that there is a positive relationship between diversification and firm performance (Bettis, A. R. & Hall, W K, (1982), Olu Ojo (2009), Mansi, S A & Reeb D M (2002)) but there are studies that resulted in opposite view which is there is negative relationship between these two variables (Lang, L HP. & Stulz, R M1994), Serveas (1996), Lins and Serveas (1999). However, the studies were mostly done in the developed country but only a few were done in developing countries or to be specific in the view of Malaysia. Thus, in this paper, researcher tries to examine the level of diversification based on selected companies chose from various sectors in Bursa Malaysia and to study its impact towards the firms performance. The level of diversification is determined by using the famous Specialization Ratios (SR) which later will classify them into three different classes whereas Return on Asset (ROA), Return on Equity (ROE) and Return on Investment (RO will be used as a proxy to measure the firms performance. The paper concludes that there is a positive relationship between levels of diversification and a firms' performance. In terms of return undiversified firms may perform better than others but in terms of riskiness highly diversified firms may have better chance in reducing it.